2018
DOI: 10.1007/s10067-017-3972-3
|View full text |Cite|
|
Sign up to set email alerts
|

Henoch-Schönlein purpura nephritis: initial risk factors and outcomes in a Latin American tertiary center

Abstract: The objective of this study was to evaluate prevalence, initial risk factors, and outcomes in Henoch-Schönlein purpura nephritis (HSPN) patients in Latin America. Two hundred ninety-six patients (validated EULAR/PRINTO/PRES HSP criteria) were assessed by demographic data, clinical/laboratorial involvements, and treatments in the first 3 months after diagnosis. They were followed-up in a Latin American tertiary center and were divided in two groups: with and without nephritis. Persistent non-nephrotic proteinur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 35 publications
1
51
0
2
Order By: Relevance
“…Shrestha et al 35 observed a similar increasing incidence of hematuria after diagnosis in their cohort of 37 adult-onset IgAV patients with hematuria from 46% of patients at baseline and to more than 66% at last visit. In a study of 322 children and adolescents with IgAV, Buscatti et al 36 reported that among those without nephritis in the first 3 months, 28% had development of renal involvement during follow-up. These findings of lateronset renal involvement suggest that active surveillance is necessary to identify patients with delayed renal pathology from IgAV.…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al 35 observed a similar increasing incidence of hematuria after diagnosis in their cohort of 37 adult-onset IgAV patients with hematuria from 46% of patients at baseline and to more than 66% at last visit. In a study of 322 children and adolescents with IgAV, Buscatti et al 36 reported that among those without nephritis in the first 3 months, 28% had development of renal involvement during follow-up. These findings of lateronset renal involvement suggest that active surveillance is necessary to identify patients with delayed renal pathology from IgAV.…”
Section: Discussionmentioning
confidence: 99%
“… Other classifications Name of classification, authors, ref. Europe Koskela et al 2017 [ 30 ] Soylemezoglu et al 2009 [ 21 ] Lucas Garcia et al 2009 [ 47 ] Mizerska-Wasiak et al 2018 [ 41 ] Gülhan et al 2015 [ 42 ] Calvo-Río et al 2013 [ 43 ] Modified semiquantitative classification Koskela et al 2017 [ 30 ] Local pathological scoring Mohey et al 2013 [ 48 ] Pillebout et al 2002 [ 49 ] The classification developed by Heaton Altugan et al 2009 [ 50 ] Classification according to Emancipator Rauta et al 2002 [ 51 ] Coppo et al 1997 [ 13 ] North America Tarshish et al 2004 [ 31 ] N/A The classification adapted from Andreoli and Bergstein Foster et al 2000 [ 52 ] The classification developed by Heaton Heaton et al 1977 [ 53 ] Meadow’s classification Meadow et al 1972 [ 54 ] Latin America Buscatti et al 2018 [ 55 ] Fuentes et al 2014 [ 56 ] de Almeida et al 2007 [ 57 ] N/A N/A Asia Inagaki et al 2018 [ 44 ] Fu et al 2016 [ 58 ] Lim et al 2016 [ 25 ] Inagaki et al 2018 [ 44 ] Xu et al 2018 [ 17 ] Kim et al 2014 [ 35 ] Japanese histologic classification Inagaki et al 2018 [ 44 ] Scoring system described by Andreoli and Bergstein Kanai et al 2011 [ 59 ] Australia N/A …”
Section: Main Textmentioning
confidence: 99%
“…The IgA vasculitis severity, particularly renal and gastrointestinal involvements, was similar between male and female patients [1,22,26]. A study from Turkey showed that renal involvement was higher in IgA vasculitis patients with scrotal involvement compared to those without this condition [22], suggesting a more severe and multisystemic disease in male patients.…”
Section: Discussionmentioning
confidence: 98%